Organisational privacy ethical care and its influence on consumer responses in smart retailing - Rohden , Simoni F. (2024)
Rohden , S. F., & Espartel, L. B. (2024). Organisational privacy ethical care and its influence on consumer responses in smart retailing: a comparison of different generations [abstract]. In Proceedings of the European Marketing Academy (pp. 1-2). Article 119727 European Marketing Academy (EMAC). https://proceedings.emac-online.org/pdfs/A2024-119727.pdf